Medical Perspectives on Brain Damage and Development. Revised - McCrae, Marcia Q.; Berks County Intermediate Unit 14, Leesport, PA.; Pennsylvania State Dept. of Education, Harrisburg ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The author describes damage and normal development of the brain, as well as assessment and intervention with brain-damaged children. After a brief introduction on the complex and delicate process of brain development and a review of incidence, aspects of etiology such as genetic and postnatal causes are discussed. Brain development is examined relative to such topics as cell migration, dendrite elaboration, and myelination. Mechanisms of brain damage covered include hemorrhage, hypoxia, and delayed response. Among suggestions given for assessment, observation of how the child functions is emphasized, a list of laboratory tests is presented, and seizures are addressed. Intervention is discussed in relation to aspects such as goals, maturation, skill development, and support for parents. (MC)
Sponsoring Agency: Office of Special Education and Rehabilitative Services (ED), Washington, DC.
Contract Number: G007802653.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Etiology; Incidence; Intervention; Medical Evaluation; Minimal Brain Dysfunction; Neurological Impairments; Physical Development; Opinion Papers; Reports, Descriptive